Prostaglandin I2 Analogs Suppress Tumor Necrosis Factor α Production and the Maturation of Human Monocyte-Derived Dendritic Cells. (1st October 2011) - Yeh, Ching-Hui; Kuo, Chang-Hung; Yang, San-Nan; Huang, Ming-Yii; Wu, Hsaing-Chi; Wang, Hsing-Pi; Kuo, Thai-Hung; Hung, Chih-Hsing
Abstract : Background: Dendritic cells (DCs) are professional antigen-presenting cells and have critical roles in regulating immune responses. Prostaglandin I2 (PGI2 ) analogs are considered to be potential treatments for asthma. However, the effect of PGI2 analogs on human monocyte-derived DCs (MDDCs) is still not clearly understood. Methods: Human MDDCs were pretreated with iloprost and treprostinil (2 PGI2 analogs) or forskolin (an adenyl cyclase activator) before lipopolysaccharide (LPS) stimulation. In some cases, I prostanoid (IP) receptor and E prostanoid receptor antagonists were added before the PGI2 analog treatment. tumor necrosis factor α (TNF-α) was measured by enzyme-linked immunosorbent assay. The expression of costimulatory molecules was assessed by flow cytometry. T-cell polarization function was investigated by measuring interferon γ, interleukin 13 (IL-13), and IL-17A production by T cells cocultured with iloprost-treated MDDCs. Results: Iloprost and treprostinil suppressed LPS-induced TNF-α expression in MDDCs. This effect could be reversed by an IP receptor antagonist, CAY10449, but not by E prostanoid receptor antagonists. Forskolin conferred a similar effect. Iloprost suppressed the LPS-induced expression of costimulatory molecules, including CD80, CD86, CD40, and HLA-DR. Iloprost-treated MDDCs increased IL-17A production by T cells. Conclusions: Prostaglandin I2 analogs may exert anti-inflammatory effects by suppressing TNF-α expression via the IP receptor-cyclic adenosine monophosphate pathways and by inhibiting the expression of costimulatory molecules in human MDDCs.